Analisis Kinerja Keuangan Perusahaan Awal Pandemi Covid -19 Ditinjau dari Rasio Keuangan (Studi Kasus Pada PT. Indosat.Tbk) - Rina Milyati Yuniastuti; Jhon Nasyaroeka (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
The research was conducted on the object of one of the telecommunications services, namely PT Indosat Ooredo Tbk. The purpose of this study was to analyze the financial performance of the Indosat Ooredo Tbk company during the Covid-19 Pandemic seen from financial ratios using standard trasnd or tendencies. The data analysis method used quantitative analysis. The financial ratios used include Profitability Ratios with Return On Assets (ROA) and Return On Equity (ROE). Liquidity Ratios in this study use current ratios or current ratios (CR) and Quick Ratios (QR). Equity Ratio (DER) and Debt to Asset ratio (DAR). The results of the study obtained that the profitability ratios and liquidity ratios of PT Indosat Ooredo Tbk had the company's performance below industry standards and in the poor category. As for the solvency ratio, the financial condition was good and the company's performance was above the industry standard.